2022
DOI: 10.1111/ctr.14614
|View full text |Cite
|
Sign up to set email alerts
|

The optimal immunosuppression management to prevent early rejection after liver transplantation: A systematic review of the literature and expert panel recommendations

Abstract: Background:The optimal immunosuppression protocol to prevent early acute cellular rejection (ACR) after liver transplantation (LT) avoiding prolonged hospitalization and early hospital readmission is undefined.Objectives: To identify the most suitable immunosuppression regimen for inclusion in ERAS programs in order to minimize early ACR after LT and to provide expert panel recommendations Data sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central.Methods: Systematic review following PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…It has been used in adult liver transplant as induction therapy. 18 Previous research in adult liver transplant has shown the use of BSA was associated with reduced incidence of acute rejection, 19 more importantly, the dose of CNIs and steroid can be reduced with BSA induction. A randomized trial has shown that combination of TAC and BAS, steroid-free immunosuppression regimen is related to improved 1-y patient and graft survival as well as reduced incidence of acute rejection in pediatric LT. 6 In our study, we did not observe the beneficial effect of BAS in recipient and graft survival rate, that is probably since none of the recipients who died was cause by rejection-related events.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in adult liver transplant as induction therapy. 18 Previous research in adult liver transplant has shown the use of BSA was associated with reduced incidence of acute rejection, 19 more importantly, the dose of CNIs and steroid can be reduced with BSA induction. A randomized trial has shown that combination of TAC and BAS, steroid-free immunosuppression regimen is related to improved 1-y patient and graft survival as well as reduced incidence of acute rejection in pediatric LT. 6 In our study, we did not observe the beneficial effect of BAS in recipient and graft survival rate, that is probably since none of the recipients who died was cause by rejection-related events.…”
Section: Discussionmentioning
confidence: 99%